Plasma modification of polylactide nonwovens for dressing and sanitary applications. Issue 1 (January 2016) - Urbaniak-Domagala, Wieslawa; Krucinska, Izabella; Wrzosek, Henryk; Komisarczyk, Agnieszka; Chrzanowska, Olga
Polylactide (PLA) non-woven surfaces were modified with Radio Frequency plasma (RF) under reduced pressure with the use of two media, air and C6 F14 vapor. The effectiveness of the plasma modification of nonwovens was analyzed by examining the fiber surface layer with ATR-FTIR absorption spectroscopy, SEM/EDX microanalysis of atomic composition, SEM surface morphology, wettability tests, susceptibility to water, and physiological liquid absorption tests and air permeability tests. The type of plasma used determines the effect obtained. Air plasma improves sorption properties of nonwovens and does not significantly affect air permeability. C6 F14 vapor plasma significantly reduces the absorption of liquids by the fabric and increases its hydrophobicity. The effects obtained from the plasma are stable for six months of fabrics storage after treatment. PLA fabrics modified with plasma can be used for various applications such as dressing and sanitary materials.